2019
DOI: 10.1177/1460458219892711
|View full text |Cite
|
Sign up to set email alerts
|

‘WP2Cochrane’, a tool linking Wikipedia to the Cochrane Library: Results of a bibliometric analysis evaluating article quality and importance

Abstract: Medical information on English Wikipedia was accessed over 2 billion times in 2018. Our goal was to develop an automated system to assist Wikipedia volunteers to improve articles with high-quality sources from journals such as The Cochrane Library. We created an automated indexing system by linking available reviews from the Cochrane library with disease-related Wikipedia articles and evaluating the relationship between the quality and importance of these articles with the number of relevant and cited Cochrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
6
0
1
Order By: Relevance
“…The WPM has formed institutional-level partnerships to provide editors with access to reputable secondary sources that are in line with the MEDRS policy on medical and health topics—namely, through its cooperation with the Cochrane Library. The Cochrane Reviews database is available to Wikipedia’s medical editors, and it offers them access to systematic literature reviews and meta-analyses summarizing the results of multiple medical research studies [ 39 ]. As well as the existence of this database on medical content, the practice of providing access to high-quality sources was also deployed specifically in regards to coronavirus in the form a list of “trusted” sources provided to volunteers of the task force on the WikiProject COVID-19 project page.…”
Section: Discussionmentioning
confidence: 99%
“…The WPM has formed institutional-level partnerships to provide editors with access to reputable secondary sources that are in line with the MEDRS policy on medical and health topics—namely, through its cooperation with the Cochrane Library. The Cochrane Reviews database is available to Wikipedia’s medical editors, and it offers them access to systematic literature reviews and meta-analyses summarizing the results of multiple medical research studies [ 39 ]. As well as the existence of this database on medical content, the practice of providing access to high-quality sources was also deployed specifically in regards to coronavirus in the form a list of “trusted” sources provided to volunteers of the task force on the WikiProject COVID-19 project page.…”
Section: Discussionmentioning
confidence: 99%
“…The WPM has formed institutional-level partnerships to provide editors with access to reputable secondary sources on medical and health topics -namely through its cooperation with the Cochrane Library. The Cochran Reviews' database is available to Wikipedia's medical editors and it offers them access to systematic literature reviews and meta-analyses summarizing the results of multiple medical research studies (34). As well as the existence of this database on medical content, the practice of providing access to high-quality sources was also deployed specifically in regards to coronavirus in the form of the task force's list of "trusted" sources.…”
Section: Discussionmentioning
confidence: 99%
“…6 More recent research, in 2019, looked at disease-related articles on Wikipedia and found that higher-quality articles were more likely to cite a Cochrane Review from the Cochrane Library than lower-quality articles on the encyclopaedia. 7 The authors used Wikipedia's definition of 'higherquality articles' as those that have inline citations from reliable sources.…”
Section: Wikipedia and Academiamentioning
confidence: 99%